The experiences of practitioners working with young people exposed to online sexual abuse - Quayle, Ethel; Schwannauer, Matthias; Varese, Filippo; Cartwright, Kim; Hewins, William; Chan, Cindy; Newton, Alice; Chitsabesan, Prathiba; Richards, Cathy; Bucci, Sandra (Frontiers in Psychiatry, 2023)
Introduction This qualitative study explored healthcare professionals' current understanding of, and clinical practices related to, Online Child Sexual Abuse (OCSA). Methods Data were collected across two UK sites (Manchester and Edinburgh). Interviews and one focus group were held with 25 practitioners working in services offering clinical support to young people who have experienced OCSA. Thematic analysis of the data identified three overarching themes and 10 subthemes related to the research questions: (1) the breadth of the problem; (2) working with OCSA; and (3) the emotionally charged nature of OCSA. Results While practitioners recognized OCSA as problematic, they differed in how they conceptualized it. There was a heightened awareness of the role that sexual images played in OCSA and concerns about first-person-produced imagery by Children and Young People (CYP). Practitioners described a generational gap related to their technology use and that of the young people they worked with. Practitioners also described a paucity of referral pathways and concerns that there was no training available to them. Organizational barriers meant that questions about technology use were not routinely included in assessments and often there was reliance on young people making disclosures. Discussion Novel findings from this study were the psychological impacts that such cases had on practitioners, which may indicate a need for organizational support for staff as well as further training needs. Existing frameworks that help conceptualize and assess the role of technology as part of the ecology of the child may have great utility for practitioners.